CONSTRUCTION, IMPLEMENTATION AND PERFORMANCE EVALUATION OF A DOT MATRIX DISPLAY DEVICE - Tsepav, Matthew; Alfa, Baba; Yakubu, Adamu; Abdullahi, Muhammad; Hassan, Omawunmi Zainab (FUDMA JOURNAL OF SCIENCES, 2023)
The technology of displaying message is an important part of communication and advertisement. The work aimed at the construction, implementation and performance evaluation of a micro-controller based scrolling display system with Bluetooth interface. The work used the micro-controller (ATmega 328p) as the control component in the construction of the device which making the design of the device simple due to the addition of the input/output port on the microcontroller. A Bluetooth module was incorporated in the design which functions as the receiver of the message sent via Bluetooth. The LED display device mainly consisted of a Bluetooth Module and Microcontroller which receives the message, checks validity and displays the received information after necessary code conversion. Hospitals, banks, sport, stadium, airports, railway stations, education sectors and stock markets find this device a useful tool by prompting them to reflect many times on the scrolling lights, automatically displaying either messages of advertisement, place description or greetings at any time of the day. The constructed device was meant to describe Physics Department by displaying the message “WELCOME TO PHYSICS DEPARTMENT” It could be used for both indoor and outdoor purposes. In fact it is the most alluring, unique, captivating and attractive means of information dissemination.